5,6-, 8,9-, 11,12- and 14,15-Epoxyeicosatrienoic Acids (EETs) Induce Peripheral Receptor-Dependent Antinociception in PGE2-Induced Hyperalgesia in Mice - Fonseca, Flavia C.S; Duarte, Igor D.G (Universitas Padjadjaran, Indonesia, 2024)
Epoxyeicosatrienoic acids (EETs) are cytochrome P450-epoxygenase-derived metabolites of arachidonic acid that act as endogenous signaling molecules in multiple biological systems, including their controversial effects on pain, including reports of the central analgesic effect and its action in inducing pain. The aim of this study was to verify the peripheral antinociceptive effect of EETs and the effect of the selective EET receptor antagonist, 14,15-EEZE, on this antinociception. The nociceptive threshold was determined by paw pressure withdrawal, and hyperalgesia was induced by intraplantar injection of PGE2 to evaluate the effect of EETs administration. EETs (5,6-, 8,9-, 11,12-, and 14,15-EET) were administered intraplantarly to male mice (n = 5). To examine the mechanism of action, a non-selective EET receptor antagonist (14,15-EEZE) was administered peripherally. Intraplantar injections of 5,6-, 8,9-, and 11,12-EET (32, 64, and 128 ng) or 14,15-EET (128, 256 and 512 ng), five minutes before the third hour after PGE2 injection induced a dose-dependent antinociceptive response. EETs showed peak action five minutes after injection, and this effect decreased concomitantly with a reduction in the nociceptive effect of PGE2 until approximately 100 min after injection (270 min after PGE2 injection). The maximum dose of each EET completely reversed the hyperalgesia induced by PGE2. The antinociceptive effect of EETs was confined to the paw that received the injection, indicating a localized effect. Intraplantar injection of the EET antagonist, 14,15-EEZE, reversed in a dose-dependent manner (32-512 ng/paw) the peripheral antinociception induced by 5,6-, 8,9-, 11,12-, and 14,15-EET. Our results provide evidence that EETs induce a peripheral antinociceptive effect and that the mechanism of action involves EET receptor activation.